2010
DOI: 10.1245/s10434-010-0939-x
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of 7th UICC N Stage for Predicting the Overall Survival of Gastric Cancer Patients After Curative Resection in China

Abstract: The 7th UICC N stage appears to provide a reliable prognostic category of MLNC of gastric cancer than the 5th/6th UICC N stage, and it is the efficiently prognostic indicator of gastric cancer after curative surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 31 publications
2
66
1
3
Order By: Relevance
“…In accordance with Deng et al, N2 and N3 patients in our study using the 6th edition system (equivalent to N3a and N3b in the 7th edition) had similar survival. 13 The studies mentioned above show that the 6th edition UICC N stage less accurately reflected patient prognosis. Therefore, our results indicated that identifying lymph node metastases and classifying patients as N3a and N3b are unnecessary.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with Deng et al, N2 and N3 patients in our study using the 6th edition system (equivalent to N3a and N3b in the 7th edition) had similar survival. 13 The studies mentioned above show that the 6th edition UICC N stage less accurately reflected patient prognosis. Therefore, our results indicated that identifying lymph node metastases and classifying patients as N3a and N3b are unnecessary.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al [28] also reported that the 7th UICC T and N stages were more evenly distributed than the 6th UICC T and N stages. Deng et al [9] reported the superiority of the 7th UICC N stage, based on the evidence of the significant difference of 5-year survival rate between N1 and N2 substages of the 7th UICC N stage and no significant prognostic difference between N2 and N3 substages of the 5th/6th UICC N stage. They argued N2 and N3 substages of the 5th/6th UICC N classification should be integrated into only one substage as N3 instead of N3a and N3b in the 7th UICC N classification.…”
Section: Discussionmentioning
confidence: 99%
“…The depth of primary tumor infiltration and number of metastatic lymph nodes (LNs) are known to be the most important prognostic factors of gastric cancer after curative surgery [3][4][5][6][7]. Especially the extent of LN metastasis is considered to be the most important independent prognostic factor [8,9]. There are two major classification systems used for gastric cancer staging: the Japanese Classification of Gastric Cancer (JCGC) and the Union Internationale Contra le Cancer (UICC)/TNM classification system.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers thought that it was not an independent prognostic factor [38][39][40], whereas others thought that younger patients has worse prognoses than elderly due to the worse biological behaviors of tumors and histological type [41]. However, Saito et al held that elderly patients had worse prognosis because they had limited lymph node dissection and lower tolerance of chemotherapy [42].…”
Section: Agementioning
confidence: 99%